Numerical study of the Epsilon TB30 aircraft frame. (November 2020) - Martins, T.; Baptista, R.; Infante, V.; Sousa, L.; Antunes, P.J.; Serrano, B.
Highlights: Estimation of fatigue life of the Epsilon TB-30 fleet. NASGRO, Forman, Walker and Paris laws were integrated to estimate fatigue crack growth. Gerber criterion and the Paris law were the most conservative fatigue life estimation approaches. NASGRO law suggests the greatest useful life. Abstract: This work has been an attempt to improve fatigue life estimation of the Epsilon TB-30 fleet of aircraft under Portuguese Air Force operation. To this end, a finite element model of the main frame was created using knowledge from strain gauges and accelerometers data as well as the loads placed on the aircraft. This model allowed the authors to identify critical areas on the structure and granted information about the stress field around these. The first estimate on fatigue life was calculated using the Miner rule coupled with several fatigue criteria. Abaqus© finite element and extended finite element method implementations were used to calculate stress intensity factors, on a crack initiating at the structure's critical hotspot. Several propagation laws (NASGRO, Forman, Walker and Paris) were integrated to estimate fatigue crack growth, using the stress intensity factor data. Material properties from the fitting of experimental data are also presented for these laws. When compared to the manufacturer's load spectrum, Portuguese Air Force operating conditions were shown to be more severe. On average the estimated Frame's fatigue life under the Portuguese Air Force loading spectrum was 30% lower. Both Gerber criterion and the Paris law were the most conservative fatigue life estimation approaches.